Endothelial GTP cyclohydrolase and tetrahydrobiopterin regulate gestational blood pressure, uteroplacental remodeling and fetal growth - Chuaiphichai, S; Yu, G; Tan, C; Whiteman, C; Douglas, G; Dickinson, Y; Drydale, E; Appari, M; Zhang, W; Crabtree, M; McNeill, E; Hale, A; et al. (American Heart Association, 2021)
Abnormal uteroplacental remodeling leads to placental hypoperfusion, causing fetal growth restriction and pregnancy-related hypertension, which are associated with endothelial dysfunction and markers of reduced vascular NO bioavailability and oxidative stress. Tetrahydrobiopterin (BH4) is a redox cofactor for eNOS (endothelial NO synthase) with a required role in NO generation. Using mice models and human samples, we investigated the physiological requirement for endothelial cell BH4 in uteroplacental vascular adaptation and blood pressure regulation to pregnancy. In pregnant mice, selective maternal endothelial BH4 deficiency resulting from targeted deletion of Gch1 caused progressive hypertension during pregnancy and fetal growth restriction. Maternal endothelial cell Gch1 deletion caused defective functional and structural remodeling in uterine arteries and in spiral arteries, leading to placental insufficiency. Using primary endothelial cells isolated from either normal or hypertensive pregnancies, we found that hypertensive pregnancies are associated with reduced endothelial cell BH4 levels, impaired eNOS activity, and reduced endothelial cell proliferation, mediated by reduced GTPCH (GTP cyclohydrolase 1) protein. In rescue experiments, high blood pressure and fetal growth restriction in pregnant endothelial cell Gch1 deficient mice was not rescued by oral BH4 supplementation, due to systemic oxidation of BH4 to dihydrobiopterin. However, the fully reduced folate, 5-methyltetrahydrofolate prevented BH4 oxidation, reduced blood pressure to normal levels, and normalized fetal growth. We identify a critical requirement for maternal endothelial cell BH4 biosynthesis in uteroplacental vascular remodeling in pregnancy. Restoration of endothelial cell BH4 with reduced folates identifies a novel therapeutic target for the prevention and treatment of pregnancy-related hypertension such as preeclampsia.